Role of Primary Agricultural Credit Co-Operative Society in Agricultural Developments: Exploring the Role of Primary Agricultural Credit Co-Operative Society in Agricultural Development (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The primary sectors driving the economic and financial development of a nation like India arecooperative banks in particular or the cooperative sector in general. The NABARD serves as the principalfunding source for primary lending institutions and is the national apex institution for agricultural loans.By providing general guidance for rural lending and financial assistance to NABARD for its functioning,the RBI plays a significant role. Since a significant majority of the population relies on agriculture, theagricultural credit plays a crucial role in both the growth of the agricultural sector specifically and thedevelopment of the whole economy generally. This paper explains how primary agricultural credit works.cooperative society for the development of agriculture.